Unusual cause of cervical lymphadenopathy in post-partum patient with atypical presentation: Kikuchi disease - Razak, Siti F. Abdul; J. K., Fong; Yunus, M. R. M.; Anastasius, Elsie J. (International Surgery Journal, 2023)
Kikuchi-Fujimoto disease, also known as histiocytic necrotising lymphadenitis, is an unusual type of painful lymphadenopathy. It is a self-limiting benign disease; usual management includes supportive therapy. We described a case of Kikuchi Disease in a childbearing-age woman who presented with painless and localised cervical lymphadenopathy during her postpartum period. Histopathology of the affected cervical node reveals areas of apoptosis and necrosis with abundant foamy histiocytes and plasmacytoid monocytes. The cervical node resolves spontaneously, and no subsequent new cervical lymph node was observed in this patient. Patient was given reassurance. It is vital to recognise Kikuchi disease as one of the causes of persistent cervical lymphadenopathy, to provide optimal management and to avoid incorrect treatment.